Information of “Jawāmi ul-Hikāyāt” by al-’Awfi on the Samanids, Karakhanids, Seljukids, and Khwarizmshahs (3) » - T.K. Beisembiev (Золотоордынское обозрение, 2015)
The article continues a series of Beisembiev’s publications [9] [13] [14] on “Jawāmi ul-Hikāyāt wa Lawāmi’ ul-Riwāyāt” by Sadid al-Din Muhammad al-‘Awfi (completed in the second quarter of the 13th century), the largest literary and historical prosaic work in Persian classical literature of pre-Mongol and Mongol periods. It contains a collection of over 2,100 stories (very poorly studied) on diverse subjects. Up to the present, a complete scholarly edition of this greatest historical source is not available. On the basis of all available publications and a MS copy of the early 14th century, Supplément Persan 95 (La Bibliothèque nationale, France), the author presents for the first time his Russian commented translation of 52 Awfi’s stories (hikayat) on Ghaznavids, Samanids, Karakhanids, Seljukids and Khorezmshahs and gives their interpretation. The titles of the stories, absent in the original, are invented by the translator. Each title is indicated by those number in parentheses, which is specified in the fundamental study on ‘Awfi by Muhammad Nizam ud-Din [40]. At the end of each story there is indicated, in square brackets, a bibliographical reference to the source, from which its translation was made. The “Repertoire” of ‘Awfi containing stories about the Samanids, Karakhanids, Seljukids and Khwarezmshahs is followed by a summarized table of all stories by ‘Awfi per-taining to these dynasties (totally 78 stories, from which 27 translated previously, with bibliographical notes to their publication). Analysis of the works on the dynasties in question by the famous academics (V.V. Bartold, V.A. Gordlevsky, C.E. Bosworth, S.G. Aghajanov, Z.M. Buniyatov, N.N. Negmatov and B.D. Kochnev) shows that, unfortunately, none of them pay due attention to the valuable information of ‘Awfi. The author hopes that his publication will provide a deeper understanding in study of Central Asian history as well as that of other regions in pre-Mongol period.